2016
DOI: 10.1021/acs.inorgchem.5b01752
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Changes to Peripheral Ligands Enable High Turnover Numbers for Photocatalytic Hydrogen Generation with Supramolecular Photocatalysts

Abstract: The photocatalytic generation of hydrogen (H2) from protons by two cyclometalated ruthenium-platinum polypyridyl complexes, [Ru(bpy)2(2,5-bpp)PtIS](2+) (1) and [Ru(dceb)2(2,5-bpp)PtIS](2+) (2) [where bpy = 2,2'-bipyridine, 2,5-bpp = 2,2',5',2″-terpyridine, dceb = 4,4'-di(carboxyethyl)bipyridine, and S = solvent], is reported. Turnover numbers (TONs) for H2 generation were increased by nearly an order of magnitude by the introduction of carboxyethyl ester units, i.e., from 80 for 1P to 650 for 2P after 6 h of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 45 publications
6
69
1
Order By: Relevance
“…The complexes reported in this contribution are part of a larger investigation of Ru/Pd and Ru/Pt dyads with various bridging (see Figure ) and peripheral ligands performed by our group under the same experimental conditions . As was observed for the compounds investigated in this contribution, the catalytic activity of these dyads in hydrogen evolution was dependent on changes to the bridging or the peripheral ligands.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The complexes reported in this contribution are part of a larger investigation of Ru/Pd and Ru/Pt dyads with various bridging (see Figure ) and peripheral ligands performed by our group under the same experimental conditions . As was observed for the compounds investigated in this contribution, the catalytic activity of these dyads in hydrogen evolution was dependent on changes to the bridging or the peripheral ligands.…”
Section: Resultssupporting
confidence: 55%
“…In a series of studies, we investigated the introduction of carboxylate groups at the peripheral ligands of Ru(bpy) 2 ‐based photosensitisers (bpy=2,2’‐bipyridine) on the photocatalytic hydrogen‐generating capacity of these molecular assemblies . The results showed that the peripheral ligands were actively involved in the catalytic activity; they determined early excited‐state processes and dramatically changed the electron flow in the photocatalyst . The bridging ligands 2,3‐dpp, 2,5‐dpp and 2,5‐bpp (Figure ) were used, and introduction of carboxylate moieties onto the peripheral ligands increased the turnover number (TON) from 0 to 400 (18 h; PdCl 2 catalyst), 0 to 44 (18 h; PtCl 2 catalyst) and 80 to 650 (6 h, PtI 2 catalyst) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Definitely, the present work provides the first photophysical evidence challenging the conventional design paradigm based on a bridging ligand acting as electron density storage reservoir. Establishing a connection between storage of electron density at the peripheral ligands at early-times and the high H 2 TON and TOF values is not straightforward considering the multiple photochemical reactions occurring at later times.…”
Section: Esi †) Indicates That the Formed 3 Mlct Manifold Ismentioning
confidence: 87%
“…EtOOCRuPt shows a significantly improved performance (TON = 650 after 6 h of irradiation at 470 nm) as compared to RuPt (TON = 80) in the same reaction conditions. [9] For RuPd, a TON of 120 was reported.…”
mentioning
confidence: 99%